Les temps passés en français dans une perspective cognitive - Kwapisz-Osadnik, Katarzyna (Neophilologica, 2007)
Making use of the notions of prototype and semantic invariants, the author of the article proposes an analysis of French past tenses and their description in the shape of semanto-cognitive schemes. An attempt to explain linguistic phenomena, especially the grammatical ones, on the basis of human cognitive abilities, that is taking into account the way he/she conceptualises reality, which is the basis for constructing an utternace, as well as their whole presentation, that is including all values, uses and functions of the categories examined, seems to be more exhaustive and more convincing in consequence.